Dynamic Evolution of Electric Vehicle Trade Network between China-Europe - Yan, Shigang; Liao, Zeng (European Scientific Journal, ESJ, 2025)
China and Europe have promoted the development of electric vehicles to reduce carbon emissions and cope with climate change. In recent years, the sales share of Chinese electric vehicle brands in the Europe market has increased rapidly, and Europe has become China’s largest export market for electric vehicles. However, the European Union implemented various temporary tariffs on Chinese electric vehicle brands in 2024, which posed a major challenge to the development of the China-Europe electric vehicle trade. Based on the social network analysis, the paper focuses on examining the dynamic evolution of the electric vehicle trade network between China and Europe from 2018-2022. The empirical results indicate a general upward trend in tighter trade groups and increased connectivity efficiency within the network, while the network density and reciprocity display some fluctuations during this period. From a structural perspective, countries that hold central positions in both centrality measures and core-periphery indicators show statistically significant convergence patterns in the electric vehicle trade network between China and Europe. This study has theoretical and practical implications, in highlighting the dynamics changes in the electric vehicle trade network between China-Europe, and providing critical insights for Chinese policymakers and Chinese electric vehicle enterprises to refine their trade strategy and enhance strategic partnerships in European countries.